Changing pattern of utilization of human donor cornea in India - Varun Gogia (Indian Journal of Ophthalmology, 2015)
Purpose: To review the changing pattern of donor, corneal utilization in an eye bank at a Tertiary Care Center in Northern India by analyzing the trend in the years 2003, 2008, and 2011. Methods: A retrospective review of eye bank records for 3 years (2003, 2008, and 2011) was performed at the National Eye Bank. Details including a clinical grade of donor cornea, indication of corneal transplantation (therapeutic or optical), type of procedure (penetrating or lamellar keratoplasty [LK]), and clinical diagnosis of the graft recipients were recorded. Primary outcome measure was to observe any preference toward LK, judicious usage of donor corneal tissue, and impact of lamellar corneal transplant in the usage of donor corneas. Secondary outcomes included overall utilization rate and change in trend of indication for keratoplasty. Results: A total of 673, 745, and 864 corneas were retrieved in the years 2003, 2008, and 2011, respectively. The percentage of donor corneal utilization increased significantly over time with the rate being 65.08%, 70.06%, and 68.29%, respectively, in the years 2003, 2008, and 2011 (P = 0.014); however, this change was reflected only in the usage of nonoptical grade corneas and not for the optical grade corneas. There was an overall increase in lamellar corneal procedures for any clinical grade of cornea (P = 0.0019); number of Descemet's stripping automated endothelial keratoplasty (DSAEK) procedures increased significantly (P < 0.001), particularly for pseudophakic corneal edema (PCE) (P = 0.0085) and failed graft (P = 0.002). Significant increase in the utilization of nonoptical grade corneas was observed over the years (P = 0.005), though the utilization did not increase significantly for optical purposes viz., LK (P = 0.08). Conclusions: Utilization rate of donor corneas increased over the years, primarily due to increase in usage of nonoptical grade corneas for therapeutic purposes. There was a procedural shift toward DSAEK for PCE and failed graft. However, an increase in usage of nonoptical grade corneas for LK, a single donor corneal tissue for two recipients, and retrieval or utilization of optical grade cornea was not observed.